PENGARUH PEMBERIAN AIR REBUSAN KACANG HIJAU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA PEKERJA BAGIAN KANTOR - Luci Riani Br Ginting; Kuat Sitepu; Arfah May Syara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Hemoglobin is a protein rich in iron. The hemoglobin molecule consists of a globin molecule, an apoprotein, and four heme groups, an organic molecule with one iron atom. The function of Hb in the blood is to carry oxygen to the lungs, to the tissues and carbon dioxide, this function depends on the amount of hemoglobin contained in red blood cells. Several nutrients are needed in the formation of red blood cells. Iron or Fe, Vitamin B12 and folic acid are the most important substances. Efforts to increase hemoglobin levels are related to the intake of foods containing iron, one of which is the provision of green bean boiled water. This service aims to determine the effect of giving boiled water mung bean to increase hemoglobin levels in office workers. The subjects in this service are 48 workers. The results of this service indicate that the workers' HB levels before giving boiled water to green beans are not normal, namely 39 (81.3%) respondents with an average obtained of 1.81. The HB levels of workers after giving boiled water of green beans were all normal HB categories as many as 48 (100%) respondents with the average obtained was 1.00. Data analysis using pre-test and post-test administration of mung bean boiled water in the experimental group showed the results where the p value was 0.000, the value was 0.000 <0.05, so it can be said that there is a significant difference between the pre-test and post-test values. which means the hypothesis is accepted. The conclusion of this service is that there is an effect of giving green bean boiled water to increase hemoglobin levels in office workers. It is hoped that health workers will provide education to the director that boiled green beans can be used as an alternative to increase hemoglobin levels.